PENGGUNAAN MEDIA AUDIOVISUAL DALAM PEMBELAJARAN MENULIS PUISI SISWA KELAS VIII SMP NEGERI 1 TAKALAR: THE USE OF AUDIOVISUAL MEDIA IN LEARNING TO WRITE POETRY OF CLASS VIII STUDENTS OF SMP NEGERI 1 TAKALAR - Bahri, Muhammad Nurul; Salam; Hasriani (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research is quantitative research which aims to: (1) describe the results of class VIII students' poetry writing skills at SMP Negeri 1 Takalar using audiovisual media. This research is a type of quantitative research. The research design used is a One-Shot Case Study Research Design. The population in this study were class VIII students of SMP Negeri 1 Takalar. The sample in this research consisted of 25 students. The data collection technique in this research is a written test technique in the form of literary works in the form of poetry. The collected data was analyzed using descriptive statistics. The results of the analysis show that: (1) students' poetry writing skills after using audiovisual media for class VIII students at SMP Negeri 1 Takalar are categorized as good with the minimum score obtained by students being 63.3, the maximum score obtained by students being 93.3 and the average score being average is 76